The Meaning and Meaningfulness of Work - the View from Sociology - Duncan Gallie; Ying Zhou (Global Labor Organization (GLO), 2025)
Since the mid-20th Century, theory and research in sociology on workers' responses to their experience of work can be broadly divided into three overlapping phases. The immediate post-war decades from the late 1940 to the 1970s saw the pervasive influence of an 'essentialist' conception of the meaningfulness of work. From the 1960s this was challenged by a 'liberal' view that rejected the idea that there was an inherent human nature in favour of an emphasis on the importance of individual value choice. It argued that a growth of instrumentalism in work orientations would make job quality decreasingly relevant to the meaning of work. Then in the first decades of the 21st Century, there was a revival of theory and research on meaningfulness, premised on the notion of fundamental human needs, but emphasising at the same time broader societal needs. These different perspectives have given a very different importance to the role of technology as a determinant of the meaning of work. Technological change was at the core of the essentialist arguments, it was marginalised by the liberal arguments and has become once more an important preoccupation of more recent work on meaningfulness.
Keywords: J24; J28; J81; 330; meaningfulness; alienation; job quality; skills; control; technology